Ag(I) and Pd(II) sensing, H- or J-aggregation and redox properties of metal-free, manganase(III) and gallium(III) phthalocyanines - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN (ELSEVIER SCI LTD, 2014)
H- or J-aggregation, Ag(I) and Pd(II) sensing and redox behaviours of novel a-substituted free-base (2), manganase(III) (3) and gallium(III) (4) phthalocyanines bearing 1-hydroxy hexane-3-ylthio moieties have been studied. H-1 NMR, FTIR, MALDI-TOF/MS, UV-Vis spectral and elemental data were used to characterize these new compounds. Upon addition of Ag(I), Pd(II), Mn(II), Co(II), Zn(II), Na(I), K(I) and Mg(II) ions to the solution of 2,3 and 4 in THF, only Ag(I), Pd(II) among them led to significant changes in their electronic absorption spectra, in particular, the Q- and the B-bands on the basis of donor acceptor interactions on the periphery in 2 and 3. Thus, in situ UV-Vis spectrotitration measurements suggested that 2 and 3 displayed high and reversible sensitivity towards Ag(I) and Pd(11) ions, as a result of the soft-metal responsive H- and J-aggregation behaviours. On the other hand, Ga(III)PcCl (4) with chlorine atoms at the axial positions and with large metal radii in the core did not show remarkable response to any ions. The binding ratio of 2 and 3 for Ag(I) was calculated as 1:1 and 1:2. AFM (Atomic Force Microscopy) was also used as complementary technique to investigate the morphology and to image the interfacial aggregates of 3. Compounds 2 and 4 showed ligand-based redox couples while 3 displayed well-defined ligand- and metal-based electrochromic processes. The existence of oxygen in solution was found to affect the redox behaviour of manganase phthalocyanine complex significantly, due to the formation of mu-oxo manganase phthalocyanine species. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; J- and H-induced aggregation; Free-base; Metal sensor; Electrochemistry; Spectroelectrochemistry; ELECTROCHEMICAL PROPERTIES; MANGANESE PHTHALOCYANINES; ZINC PHTHALOCYANINES; SPECTROELECTROCHEMISTRY; CHEMOSENSORS; COORDINATION; DERIVATIVES; COMPLEXES; BEHAVIOR; HYBRID